A new species of Geodiscelis Michener & Rozen (Hymenoptera: Colletidae: Xeromelissinae) from Peru - Ferrari, Rafael R. (Zootaxa, 2015)
A new species of the bee genus Geodiscelis Michener & Rozen, 1999, G. antiminera sp. nov., is here described and illustrated. This is the sixth species of the genus, and the second recorded from Peru. The combination of malar area 1.5x longer than wide, wing veins dark-brown, metepisternum nearly glabrous, and medioventral process on gonocoxa conical and well-developed, separates G. antiminera sp. nov. from all other Geodiscelis species. An updated identification key for all known species is provided. Phylogenetic analyses show that G. antiminera sp. nov. belongs to the subgenus Nazcoediscelis Packer & Dumesh, 2014 and is sister to the other three species in the subgenus.